(untitled) (Al-Qamar, 2026)
The expansion of religious extremism in Pakistan entails an intricate reaction of sectarian polarization, religious politicization, geopolitical conflict, educational fragmentation, and the selective misuse of Islamic texts. Since extremist actors often use the Qur’an to identify the reasons to commit violence, exclusion, and takfīr, such positive actions should not avoid interacting with Islamic sources but act to address them. This paper claims that the Qur’an does include a consistent peacebuilding ethic that can be used as an Islamic counter-virality to religious extremism in Pakistan. The article presents justice, reconciliation, mercy, forgiveness, restraint, consultation, and human dignity as the principal Qur’anic principles applicable to counter-extremist efforts through a qualitative design that relies on textual analysis of the major themes of the Qur’an, discourse analysis of the lecture and writing of Pakistani Islamic scholars, and their public discourse. It also reveals that mainstream Pakistani scholars of various orientations generally oppose terrorism, have a negative stance on the unjustifiable violence, and advocate contextualized understandings of jihad and anti-takfīr discourse. The article concludes that Qur’anic ethics can reinforce the counter-extremism agenda in Pakistan when strategized in education, discourse in mosques, communal peace building, and mass policy. By bridging Islamic scripture, religious authority, and the modern needs of peace building, this study adds to the literature on religion and violence, Islamic ethics, and culturally based counter-extremism.